(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Over the last few years, life has changed for everyone. The COVID-19 pandemic has taken many lives, changed working patterns, and introduced a new normal in our lives. The new normal has introduced work from home, social distancing, alternate working hours, and much more. Employees’ expectations of their job have been changed. The mindset of family life after retirement has perished. Uncertainty of life has suggested that family life is as important as a career. People now don’t look for jobs that are high paying but they are seeking a balance. The present study is an effort to understand the work-life balance among bank employees. Researchers have surveyed SBI and ICICI employees to know their work-life balance status among them. The present study finds the contemporary work-life balance in public and private sector banks in India. The finding of the research suggests that work-life balance is not so good among bank employees. Though there are some advantages in public sector banks and a few others in private sector banks overall employees need reform at both ends.